2019
DOI: 10.1096/fj.201801385rr
|View full text |Cite
|
Sign up to set email alerts
|

A miR‐29a‐driven negative feedback loop regulates peripheral glucocorticoid receptor signaling

Abstract: The glucocorticoid receptor (GR) represents the crucial molecular mediator of key endocrine, glucocorticoid hormone–dependent regulatory circuits, including control of glucose, protein, and lipid homeostasis. Consequently, aberrant glucocorticoid signaling is linked to severe metabolic disorders, including insulin resistance, obesity, and hyperglycemia, all of which also appear upon chronic glucocorticoid therapy for the treatment of inflammatory conditions. Of note, long‐term glucocorticoid exposure under the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 87 publications
0
23
0
Order By: Relevance
“…The analysis of improved bone mineral density and trabecular morphology in miR-29aTg mice explained the requirement of considerable energy expenditure for preserving osteoblast function and microstructure integrity, which prevented HFD-induced bone mass loss. Expanding studies have revealed that miR-29a signaling regulates lipid metabolism in the muscles of diabetic mice [38] and delays fatty liver development in HFD-fed mice [39], as well as inhibits adipocyte formation of human adipose mesenchymal stem cells [40]. We uncovered mild marrow adiposis together with moderate visceral adipose deposit in miR-29aTg mice.…”
Section: Discussionmentioning
confidence: 82%
“…The analysis of improved bone mineral density and trabecular morphology in miR-29aTg mice explained the requirement of considerable energy expenditure for preserving osteoblast function and microstructure integrity, which prevented HFD-induced bone mass loss. Expanding studies have revealed that miR-29a signaling regulates lipid metabolism in the muscles of diabetic mice [38] and delays fatty liver development in HFD-fed mice [39], as well as inhibits adipocyte formation of human adipose mesenchymal stem cells [40]. We uncovered mild marrow adiposis together with moderate visceral adipose deposit in miR-29aTg mice.…”
Section: Discussionmentioning
confidence: 82%
“…If miR-29a serves as a physiologically relevant regulator of leptin in humans, our findings suggest that miR-29a should be reduced in obese patients. Indeed, previously published work demonstrates that in a cohort of 66 men and women, ranging from lean to obese, miR-29a in visceral and subcutaneous WAT is negatively correlated with BMI 20 . A second human study found an increase in miR-29a in subcutaneous WAT from 19 obese individuals following diet and exercise-induced weight loss 29 .…”
Section: Figmentioning
confidence: 94%
“…1k). miR-29 has been described previously as a regulator of the glucocorticoid receptor in adipocytes 20 , but has otherwise not been well studied in fat cells. Of the three miR-29 family members, miR-29a is 60-70 fold more abundant in adipose tissue than miR-29b and miR-29c (Supplementary Fig.…”
Section: Figmentioning
confidence: 99%
“…Similarly, transfection of miR-331-3p mimic promotes CS sensitivity in several transformed cell lines by inhibiting JKN phosphorylation ( Lucafo et al, 2020 ). Other pro-CSR miRNAs are miR-21, miR-29a and miR-222; conversely, miR-15b, miR-16, and miR-128b promote CS sensitivity in cancer cells ( Kotani et al, 2009 ; Rainer et al, 2009 ; Wang et al, 2011 ; Glantschnig et al, 2019 ; Xu et al, 2019 ). Evidence for both pro- and anti-CSR effects of miR-221 and miR-124 has been reported ( Kotani et al, 2009 ; Lv et al, 2012 ; Kim et al, 2015 ; Liang et al, 2017 ; Xu et al, 2019 ).…”
Section: Mirnas and Their Role In Vkh Etiology And Treatmentmentioning
confidence: 99%